Feeding Value of Hybrid Napier Silage Incorporated with Lactobacillus plantarum in Crossbred Heifers in Kerala - K. A. Akhil Prasad, K. Nayana; M. T. Dipu (Indian Journal of Animal Nutrition, 2025)
An experiment was carried out to assess the feeding value of grass silage incorporated with bacterial inoculum in crossbred heifers. Silage was prepared using hybrid Napier grass incorporated with Lactobacillus plantarum (GSL) at a concentration of 1 x 105 CFU per gram and ensiled for a period of 21 days.  An in vivo feeding trail was conducted using twelve crossbred heifers for a period of thirty days. The animals were divided into two groups with six animals each and were allotted into two dietary treatments, T1 (Concentrate + fodder grass as control ration) and T2 (Concentrate + GSL). A digestibility trial of five days duration was conducted at the end of feeding trial. Body weight and serum biochemical parameters recorded at the start and end of the feeding trail were statistically similar between two treatment groups. The digestibility coefficient of dry matter and CP were similar between treatment groups. From the overall results, it can be concluded that hybrid Napier grass, ensiled for 21 days using L. plantarum can be effectively used for rearing of crossbred heifers without compromising the growth performance.